Microcavity properties of 2D photonic crystal made by silica matrix doped with magnetic nanoparticles. (January 2016) - Moukhtari, R; Hocini, A; Khedrouche, D
Abstract: In this present paper, quality factor of two-dimensional magneto-photonic crystals microcavity fabricated by SiO2/ZrO2 or SiO2/TiO2 matrix doped with magnetic nanoparticles, in which the refractive index varied in the range of 1.51 to 1.58, has been investigated. Finite difference time domain method (3D FDTD) with perfectly matched layers (PML) was used to calculate the transmission spectrum. We demonstrate that the Q factor for the designed cavity increases as the refractive index increases, and found that the Q factor decreases as the volume fraction VF% increases. The obtained results are useful for better designs of magneto photonic crystal devices.